How did fairytales become a genre of Croatian children's literature? - Hameršak, Marijana (Primerjalna književnost, 2012)
This article compares the communication circuits of the oldest fairytales in Croatian children's literature, focusing on their production and distribution, and on the historically specific social and cultural aspects of books as material objects.
Keywords: hrvaška književnost; zgodovina knjige; otroška književnost; children's literature; 19. st.; pravljice; založništvo; knjižni trg